2020
DOI: 10.2174/1871520619666190702145609
|View full text |Cite
|
Sign up to set email alerts
|

Design, In Silico Modelling, and Functionality Theory of Novel Folate Receptor Targeted Rutin Encapsulated Folic Acid Conjugated Keratin Nanoparticles for Effective Cancer Treatment

Abstract: Objective: Site-specific and toxic-free drug delivery, is an interesting area of research. Nanoengineered drug delivery systems possess a remarkable potential for effective treatment of various types of cancers. Methods: In this study, novel Folic Acid (FA) conjugated keratin nanoparticles (NPs) were assembled with encapsulation and delivery of Rutin (Rt) into breast cancer cells through the overexpressed folate receptor. The biocompatible, Rt encapsulated FA conjugated keratin NPs (FA@Ker NPs) were successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…[4] Based on the data generated by such in silico analyses, nanotechnology-based therapeutic approaches could be improved. [51][52][53] Among 2D materials, GO is the most studied one using such computational models to depict interactions with various biological moieties, mainly proteins. [54][55][56][57][58][59][60][61] For example, Baweja et al reported that GO and reduced GO (rGO) were able to inhibit the α-helix to β-sheet transition of amyloid beta (Aβ) peptide, which has been implicated in the pathogenesis of Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Based on the data generated by such in silico analyses, nanotechnology-based therapeutic approaches could be improved. [51][52][53] Among 2D materials, GO is the most studied one using such computational models to depict interactions with various biological moieties, mainly proteins. [54][55][56][57][58][59][60][61] For example, Baweja et al reported that GO and reduced GO (rGO) were able to inhibit the α-helix to β-sheet transition of amyloid beta (Aβ) peptide, which has been implicated in the pathogenesis of Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed that rutin encapsulated in folic acid conjugated keratin nanoparticles significantly increased the level of ROS, which led to cell death in MCF-7 breast cancer cell lines while exhibiting less toxicity in normal cells. Furthermore, the nanoparticles enhanced the uptake of rutin in MCF-7 cells 36 . Quercetin easily passes through the colon barrier as a rutin metabolite and leads to biological effects.…”
Section: Discussionmentioning
confidence: 94%
“…Rutin encapsulated in folic acid conjugated keratin NPs promotes cell death in MCF-7 breast cancer cells while exhibiting less toxicity in healthy cells [ 230 ] ( Table 2 ). Additionally, the actively targeted nanoformulation decreases tumor cell migration, elevates rutin uptake in cancer cells, and boosts apoptosis through ROS production and mitochondrial potential loss.…”
Section: Nanostructured Formulations Of Rutin In Combating Cancermentioning
confidence: 99%
“…Additionally, the actively targeted nanoformulation decreases tumor cell migration, elevates rutin uptake in cancer cells, and boosts apoptosis through ROS production and mitochondrial potential loss. An in vitro study indicated that the nanoformulation selectively targets breast cancer cells [ 230 ]. However, in vivo studies are needed to confirm the active targeted delivery of folic acid conjugated keratin NPs.…”
Section: Nanostructured Formulations Of Rutin In Combating Cancermentioning
confidence: 99%